Performance enhancement of lithium-ion battery using modified LiMn2O4 cathode followed by ultrasonic-assisted electrochemically synthesized graphene - Md Ramjan Ali; Mohammad Asaduzzaman Chowdhury; Md Mostafizur Rahman; Md Osman Ali; Saifullah Mahmud; Md Masud Rana; Biplov Kumar Roy (Results in Engineering, 2023)
Herein, the LiMn2O4 (LMO) cathode was modified using ultrasonic-assisted electrochemically synthesized graphene to enhance lithium-ion batteries' charging and discharging performance. Graphene was synthesized from graphite using an electrochemical exfoliation process in which 0.1 M molar (NH4)2SO4 was utilized as the electrolyte with +10 to +12V DC power, followed by ultrasonication in acetone for 2 h. The FESEM, EDX, XRD, Raman, FTIR, UV–vis, and TGA results suggested that ultrasonically treated graphene (EG1) is superior to electrochemically exfoliated graphene (EG2). Thus, EG1 was used to modify the LMO cathode to fabricate lithium-ion batteries. Afterward, the electrochemical performances of the LMO and LMO/EG1 cathode batteries were investigated. Surface morphological analysis revealed that EG1 is composed of two-dimensional, planar, brighter, and less oxidized graphene nanosheets with an average particle size of 18.02 nm. XRD results exhibited that EG1 has a smaller crystalline size and a thinner average stacking thickness of its layered structure than EG2. According to Raman analysis, the intensity ratio I2D/IG of EG2 and EG1 were 0.70 and 0.81, respectively, deduced that both are multi-layered graphene structures; however, EG1 contains a lesser number of graphene layers than EG2. The electrochemical analysis showed that LMO/EG1 cathode batteries have 89 % coulombic efficiency at 0.1C, while LMO batteries have only 81 %. The discharge capacity retention rate of the LMO batteries was 71.4 %, while it was 94.8 % for LMO/EG1 after observing 100 cycles at 0.1 C. Therefore, LMO/EG1 has excellent cycle stability and electrochemical performance and could potentially enhance the performance in hybrid automotive and electronic devices.